Public versus Private Education with Risky Human Capital - Fabian Kindermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper studies the long-run macroeconomic, distributional and welfare effects of tuition policy and student loans. We therefore form a rich model of risky human capital investment based on the seminal work of Heckman, Lochner and Taber (1998). We extend their original model by variable labor supply, borrowing constraints, idiosyncratic wage risk, uncertain life-span, and multiple schooling decisions. This allows us to build a direct link between students and their parents and make the initial distribution of people over different socio-economic backgrounds endogenous. Our simulation indicate that privatization of tertiary education comes with a vast reduction in the number of students, an increase in the college wage premium and longrun welfare losses of around 5 percent. Surprisingly, we find that from privatization of tertiary education, students are better off compared to workers from other educational classes, since the college wage premium nearly doubles. In addition, our model predicts that income contingent loans on which students don't have to pay interest, improve the college enrolment situation for agents from all kinds of backgrounds.
Keywords: I22; J24; H52; 330; public vs. private education; schooling choice; human capital investment; idiosyncratic uncertainty